Poster 154: MLB Player Workload and Performance Following Arthroscopic Shoulder Labral Repair. Issue 7 (30th July 2022) - Cotter, Daniel; Lau, Emily; Abbas, Muhammad; Kadouh, Ali; Fehmi, Ziad; Jildeh, Toufic; Moutzouros, Vasilios; Castle, Joshua
Objectives: To investigate the impact of arthroscopic shoulder labral repair on return to play (RTP), career longevity, workload, and performance of Major League Baseball (MLB) athletes Methods: A retrospective review of MLB players after arthroscopic shoulder labral repair from 2004-2018 was performed. A 2:1 control group matched by demographic information was used. Demographics, workload, and performance metrics were collected. Statistical analysis examined workload/performance at one and three-years after injury compared to one-year before. Workload/performance percentage relative to baseline was also compared. Results: 26/ 39 (66%) pitchers and 18/25 (72%) positional players RTP and were matched with 54 and 34 controls, respectively. Following surgery, players experienced shorter careers (2.3 ± 2.6 vs 5.8 ± 2.8, p<0.001, pitchers), (2.9 ± 2.5 vs 5.3 ± 2.3, p=0.002, positional players). One-year post-index, pitchers had reduced games played (GP) (22.0 ± 21.3 vs 32.1 ± 21.0, p=0.002), started (15.0 ± 14.1 vs 6.1 ± 6.5, p =0.0038), and innings (109.5 ± 73.2 vs 44.7 ± 29.3, p =0.0004), and increased walks/hits-per-inning-pitched (WHIP) (1.3 ± 0.2 vs 1.5 ± 0.3, p =0.0035). One-year post-index, positional players had reduced GP (98.0 ± 50.7 vs 75.7 ± 47.1, p =0.0399), innings (778.9 ± 431.6 vs 528.6 ± 429.9, p =0.0263), on-base-percentage (OBP) (0.3 ± 0.1 vs 0.3 ± 0.1, p =0.0116), and on-base-plus-slugging-percentage (OPS) (0.7 ± 0.2 vs 0.6 ± 0.2, p =0.0281). Both pitchers and positional players experienced no reduction in any metric at three-years post-index. Compared to controls, pitchers had decreased GP (50 ± 40 vs 150 ± 180, p <0.001) and innings (40 ± 30 vs 150 ± 190, p <0.001), with increased WHIP when calculated as a percentage from baseline (120 ± 20 vs 100 ± 20, p =0.027) one-year post-index. Positional players had decreased OBP (80 ± 30 vs 110 ± 40, p =0.017) and OPS (80 ± 30 vs 100 ± 20, p =0.019) from baseline one-year post-index and decreased OBP three-years post-index (90 ± 20 vs 100 ± 20, p =0.017). Conclusions: Following RTP after arthroscopic shoulder labral repair, MLB players had reduced career longevity and workload/performance one-year post-index, but these stats returned towards baseline at three-years post-index. Figure I. Relative Percentage of Game Utilization and Performance (A) One Season and (B) Three Seasons Following RTP from Arthroscopic Shoulder Labral Surgery for MLB Pitchers Pre-index baseline is represented by the horizontal line (100%) across all variables. Relative percentages below this line indicate that the post-index variable was less than baseline. *P < 0.05: indicates significant differences between labral surgery and control groups Abbreviations: WHIP, walks/hits per inning pitched; ERA, earned run average Figure II. Pitcher and Positional Player Relative Percentage of Workload and Performance One-Season Following RTP from Arthroscopic Shoulder Labral Repair Pre-index baseline represented by horizontal line (100%) across all variables. Relative percentages below this line indicate post-index variable was less than baseline. *P<0.05 Table I. Demographics Table II. Workload and Performance one-Year Before and After Labral Surgery